2013
DOI: 10.1063/1.4815836
|View full text |Cite
|
Sign up to set email alerts
|

Storage-ring measurements of hyperfine induced transition rates in berylliumlike ions

Abstract: Articles you may be interested inMassively parallel implementations of coupled-cluster methods for electron spin resonance spectra. I. Isotropic hyperfine coupling tensors in large radicals

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Figure 5 summarizes the state-of-the-art for electron-ion recombination of W 20+ ([Kr] 4d 10 4 f 8 ). As in the case of isoelectronic Au 25+ , the measured merged-beam rate coefficient (Schippers et al 2011) at low electron-ion collision energies is more than two orders of magnitude larger than the theoretical rate coefficient for RR. Up to energies 2011) from the TSR storage ring.…”
Section: Exotic Recombination Pathwaysmentioning
confidence: 64%
See 4 more Smart Citations
“…Figure 5 summarizes the state-of-the-art for electron-ion recombination of W 20+ ([Kr] 4d 10 4 f 8 ). As in the case of isoelectronic Au 25+ , the measured merged-beam rate coefficient (Schippers et al 2011) at low electron-ion collision energies is more than two orders of magnitude larger than the theoretical rate coefficient for RR. Up to energies 2011) from the TSR storage ring.…”
Section: Exotic Recombination Pathwaysmentioning
confidence: 64%
“…Accurate atomic data are required for the modeling of radiation losses from the fusion plasma due to impurity ions, and recombination rate coefficients for tungsten ions are of particular concern (Pütterich et al 2008). For W 20+ (Schippers et al 2011) and W 18+ (Spruck et al 2014) it was found that in the temperature ranges where these ions form in a collisionally ionized plasma the experimentally derived plasma recombination rate coefficients exceed the ones from the ADAS atomic data base (ADAS 2014) by up to an order of magnitude. below ∼ 10 eV the result of the standard DR calculation of Badnell et al (2012, full curve) is a factor of three lower than the experimental curve.…”
Section: Exotic Recombination Pathwaysmentioning
confidence: 93%
See 3 more Smart Citations